Conceptual approach to the term "Diseasogenic," from an urban planning perspective - Martínez-Castrejón, Mariana; Covarrubias-Melgar, Felipe; Tapia-Guillén, Franco; Verónica-Gasga, Cristiana (Gestionar: revista de empresa y gobierno, 2023)
The rapid urban growth in the Anthropocene poses social challenges for well-being. The term "diseasogenic," originating from the Global North, highlights the relationship between cities and health. The objectives of this study were i) to propose the concept of "pathogenic city" as equivalent to "diseasogenic" based on academic publications from the Global South and ii) to provide a unified operational definition within the framework of urban planning. In this systematic review, using Google Scholar, the content of 7 English-language scientific publications containing "diseasogenic" and 9 Spanish-language publications containing "entornos patógenos" and "ciudad patógena" was analyzed from 27 and 16 initially detected scientific publications, respectively. In English, 3 conference papers, 2 book chapters, 1 scientific article, and 1 review article were analyzed. In Spanish, 9 scientific articles were reviewed. This state-of-the-art review on the application, usage, and operational definition of the term ’diseasogenic’ from an urban-architectural perspective is a qualitative, descriptive, and exploratory investigation. The results revealed the relationship between "diseasogenic" and "pathogenic city" and their interaction with urban planning and citizen health management. It is concluded that an emerging definition of urban pathologies fosters identification between the Global North and South, recognizing points of convergence in the impacts of cities on urban and individual health of their occupants regardless of the hemisphere they inhabit.